Applications to Support Smart Learning Environments in Project-Based Cooperative Learning Models in Java Programming Courses and Applied in Science - Rika Melyanti; Fitri Ayu; Mardainis Mardainis; Zupri Henda; Herianto Herianto (Jurnal Penelitian Pendidikan IPA, 2024)
This research paper proposes the development of an application to support an intelligent learning environment in a project-based cooperative learning model on Java programming courses. The application is built using the Laravel framework where the end result later lecturers can easily see the student portfolio of each learning access on the java programming course. An intelligent learning environment will enable students to learn from their experiences, adapt to new input, and perform project tasks already assigned to lecturers. This application will also help teachers in groups that are adapted from the cooperative learning model of the STAD type. The proposed application will be designed to make it easier for teachers to form groups based on the ability of students from high, medium and low, so that the groups formed are not homogeneous groups. This application will be useful for a variety of study programmer that have practical programming courses devised. This paper will discuss the benefits of cooperative learning, project-based learning, and intelligent learning environments in the context of Java programming courses. It will also provide insights into the proposed application development process.  This application facilitates communication and discussion among students in a group that is easily connected with their lecturer, so that the lecturer can also monitor the activity of the group members. This paper will conclude with a discussion of the potential impact of the proposed applications on the field of education and the future in the learning environment.